Randomly Amplified DNA Fingerprinting: A Culmination of DNA Marker Technologies Based on Arbitrarily-Primed PCR Amplification. Issue 3 (1st November 2002) - Waldron, Julie; Peace, Cameron P.; Searle, Iain R.; Furtado, Agnelo; Wade, Nick; Findlay, Ian; Graham, Michael W.; Carroll, Bernard J.
Abstract : Arbitrarily-primed DNA markers can be very useful for genetic fingerprinting and for facilitating positional cloning of genes. This class of technologies is particularly important for less studied species, for which genome sequence information is generally not known. The technologies include Randomly Amplified Polymorphic DNA (RAPD), DNA Amplification Fingerprinting (DAF), and Amplified Fragment Length Polymorphism (AFLP). We have modified the DAF protocol to produce a robust PCR-based DNA marker technology called Randomly Amplified DNA Fingerprinting (RAF). While the protocol most closely resembles DAF, it is much more robust and sensitive because amplicons are labelled with either radioactive 33 P or fluorescence in a 30-cycle PCR, and then separated and detected on large polyacrylamide sequencing gels. Highly reproducible RAF markers were readily amplified from either purified DNA or alkali-treated intact leaf tissue. RAF markers typically display dominant inheritance. However, a small but significant portion of the RAF markers exhibit codominant inheritance and represent microsatellite loci. RAF compares favorably with AFLP for efficiency and reliability on many plant genomes, including the very large and complex genomes of sugarcane and wheat. While the two technologies detect about the same number of markers per large polyacrylamide gel, advantages of RAF over AFLP include: (i) no requirement for enzymatic template preparation, (ii) one instead of two PCRs, and (iii) overall cost. RAF and AFLP were shown to differ in the selective basis of amplification of markers from genomes and could therefore be used in complementary fashion for some genetic studies.